Synchrotron radiation and X‐ray free‐electron lasers (X‐FELs) explained to all users, active and potential. (2nd May 2021) - Hwu, Yeukuang; Margaritondo, Giorgio
Abstract : A new teaching strategy presents synchrotron sources and free‐electron lasers (FELs) in a form accessible to readers without a theoretical physics background. This specifically includes the microbunching and amplification mechanisms of FELs. Abstract : Synchrotron radiation evolved over one‐half century into a gigantic worldwide enterprise involving tens of thousands of researchers. Initially, almost all users were physicists. But now they belong to a variety of disciplines: chemistry, materials science, the life sciences, medical research, ecology, cultural heritage and others. This poses a challenge: explaining synchrotron sources without requiring a sophisticated background in theoretical physics. Here this challenge is met with an innovative approach that only involves elementary notions, commonly possessed by scientists of all domains.